Equity, Equal Shares or Equal Final Outcomes? Group Goal Guides Allocations of Public Goods - Kazemi, Ali; Eek, Daniel; Gärling, Tommy (Frontiers in Psychology, 2017)
In an experiment we investigate preferences for allocation of a public good among group members who contributed unequally in providing the public good. Inducing the group goal of productivity resulted in preferences for equitable allocations, whereas inducing the group goals of harmony and social concern resulted in preferences for equal final outcomes. The study makes a contribution by simultaneously treating provision and allocation of a public good, thus viewing these as related processes. Another contribution is that a new paradigm is introduced that bears closer resemblance to real life public good dilemmas than previous research paradigms do.